From afterthought to forefront: Transforming agricultural resilience through co-designed socio-technical innovations - Lutomia, Cosmas Kweyu; Ketema, Dessalegn Molla; Nchanji, Eileen Bogweh (2024)
Most current socio-technical innovation bundling (STIB) approaches addressing climate change challenge in agri-food systems are designed in unsystematic manner. They lack deliberate efforts that combine social, technical, and technological innovations in an effective way. The perspectives of diverse groups, such as women, youth, or marginalized communities, are rarely considered during bundling or are treated as an afterthought, resulting in inequitable outcomes. While bundling of innovations is recognized as critical to enhancing agri-food resilience, there is limited systematic evidence on their effectiveness in different contexts. Why socio-technical innovation bundling? What are the processes and the effects on productivity, empowerment, and resilience